Predicting the energy consumption of heated plastic greenhouses in south-eastern Spain - Lopez, J.C.=700 1 Baille, A.; Bonachela, S.; Gonzalez Real, M.M.; Perez Parra, J.
(Es, En)
ilus., 21 ref.
Keywords: CONSUMO DE ENERGIA; CALENTAMIENTO; INVERNADEROS; PHASEOLUS VULGARIS; TEMPERATURA; ESPAÑA